Differences in neural responses to reward and punishment processing between anorexia nervosa subtypes: An fMRI study. Issue 9 (19th June 2017) - Murao, Ema; Sugihara, Genichi; Isobe, Masanori; Noda, Tomomi; Kawabata, Michiko; Matsukawa, Noriko; Takahashi, Hidehiko; Murai, Toshiya; Noma, Shun'ichi
Abstract : Aim: Anorexia nervosa (AN) includes the restricting (AN‐r) and binge‐eating/purging (AN‐bp) subtypes, which have been reported to differ regarding their underlying pathophysiologies as well as their behavioral patterns. However, the differences in neural mechanisms of reward systems between AN subtypes remain unclear. The aim of the present study was to explore differences in the neural processing of reward and punishment between AN subtypes. Methods: Twenty‐three female patients with AN (11 AN‐r and 12 AN‐bp) and 20 healthy women underwent functional magnetic resonance imaging while performing a monetary incentive delay task. Whole‐brain one‐way analysis of variance was conducted to test between‐group differences. Results: There were significant group differences in brain activation in the rostral anterior cingulate cortex and right posterior insula during loss anticipation, with increased brain activation in the AN‐bp group relative to the AN‐r and healthy women groups. No significant differences were found during gain anticipation. Conclusion: AN‐bp patients showed altered neural responses to punishment in brain regions implicated in emotional arousal. Our findings suggest that individuals with AN‐bp are more sensitive to potential punishment than individuals with AN‐r and healthy individuals at the neural level. The present study provides preliminary evidence that there are neurobiological differences between AN subtypes with regard to the reward system, especially punishment processing.